What do we know about the global financial safety net? Data, rationale and possible evolution - Beatrice Scheubel; Risto Herrala; Livio Stracca (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We critically review the theoretical basis for the provision of global financial safety nets (GFSN) and provide a comprehensive database covering four types (foreign exchange reserves, IMF financing, central bank swap lines, and Regional Financing Arrangements) for over 150 countries in the sample 1970-2015. We also show some key stylised facts associated with the provision of financing associated with GFSN and compare macroeconomic outcomes around sudden stop episodes depending on how much GFSN were available for countries, and used. We conclude with some speculations on the possible evolution of the GFSN.
Keywords: F34; F33; G01; 330